Investigating subject matter knowledge and pedagogical content knowledge in mathematics with the Concept Cartoons method - Libuše Samková (Karolinum Press, 2020)
The article focuses on an educational tool called Concept Cartoons and its possible use in professional preparation of future primary school teachers. In particular, it presents the method of how Concept Cartoons can be employed as a tool for diagnosing subject matter knowledge and pedagogical content knowledge in mathematics. The first part of the contribution introduces the concept of teachers' knowledge that is used in the article, and the Concept Cartoon tool. It describes the original Concept Cartoons method for classroom use at primary and secondary school levels that was established by Keogh and Naylor, and then it introduces our work on diagnostic Concept Cartoons method, including a commented summary of our recent research on qualitative diagnosis of subject matter knowledge and pedagogical content knowledge in mathematics. The second part of the contribution introduces another step in the methodology, a mixed approach to the issue that enables to enrich the qualitative results with quantitative characteristics. The mixed method is illustrated through a small empirical study that shows how exactly the quantitative enrichment might be provided.